Simulation Analysis of Cutting Force and Temperature Dynamic Characteristics During Gear Skiving Process - Gang Li; Yongpeng Chen; Yong Yang (Jixie chuandong, 2022)
Based on the principle of double-degree-of-freedom meshing with interleaved axes in space， the material removal process is complicated，and the cutting force and temperature change dynamically during the cutting process. Thus，a finite element simulation analysis model of the gear skiving process is established，and the constitutive model and fracture criterion of the workpiece material suitable for the simulation analysis of the gear skiving process are determined through comparison and analysis，so as to realize the accurate prediction of the dynamic change process of the cutting force and the cutting temperature. On this basis， the influence of different tool speeds and axial feed rates on the three-direction cutting force and cutting temperature is analyzed. The research results can provide method support for the analysis and optimization of the gear skiving technology.